Wellbeing determinants of household’s ability to make ends meet – A hierarchical regression model for Abu Dhabi - Badri, Masood; Aldhaheri, Hamad; Alkhaili, Mugheer; Yang, Guang; Albahar, Muna; Alrashdi, Asma; Alsawai, Alanoud (Innovation Journal of Social Sciences and Economic Review, 2022)
The purpose of this study is to explore the key factors influencing the ability of households in Abu Dhabi to maintain a subsistence standard of living, particularly focusing on how various socio-demographic and well-being determinants impact this ability. The study utilizes data from 38,124 employed heads of households who participated in the Abu Dhabi Quality-of-Life (QoL) survey conducted in 2021. A hierarchical regression model was applied to analyze the relationships between the ability to make ends meet and a range of independent variables while controlling for specific household and individual characteristics. The findings reveal that satisfaction with household income, the ability to save from previous earnings, and work-family balance are the most significant determinants of a household’s ability to make ends meet. Additionally, the education level of the head of the household and the presence of a financial plan also play crucial roles. The results suggest that while the hierarchical regression model offers valuable insights, it does not fully capture the directional relationships between the variables, indicating the need for further research. In conclusion, the study highlights the importance of income satisfaction, financial planning, and work-life balance in helping households achieve financial stability. The implications for policymakers include the need to develop targeted strategies that enhance financial literacy, support income satisfaction, and promote work-life balance to improve the overall well-being of households in Abu Dhabi. Future research should consider a longitudinal approach to better understand the causal relationships between these factors and the ability to make ends meet.
Keywords: Ability to make ends meet; Financial capability; Households; Well-being; COVID-19; Abu Dhabi